From Jokes to Harm: A Critical Discourse Analysis of Humor and Harassment in TikTok Comment Sections - Loeis, Jhonson; Lubis, Heri Setiawan; Harianja, Alvernod Andreas; Dachi, Paulus; Habib, Reyhan; Putri, Dian Marisha (Journal of English Language and Education, 2026)
This study examines how humor in TikTok comment sections can gradually transform into discriminatory and verbally aggressive discourse. While online humor is often perceived as harmless entertainment, limited research has examined how repeated joking practices on TikTok contribute to the normalization of ethnic stereotypes and subtle harassment. Using Critical Discourse Analysis (CDA) supported by microaggression theory and Goffman’s concept of face-threatening acts, this study analyzes a total of 18 comments collected from five viral TikTok videos, selected based on their high engagement, public visibility, and the presence of controversial identity-based humor. The data were documented through screenshot-based qualitative collection to preserve original linguistic features. The findings reveal recurring patterns of ethnic labeling, blame attribution, and dehumanizing humor that function as microaggressions and reinforce social hierarchies. Beyond identifying linguistic patterns, this study highlights important implications for digital literacy, ethical online participation, and the need for stronger content moderation to prevent humor from becoming a socially accepted form of harassment.